Carotid arterial wall inflammation in peripheral artery disease is augmented by type 2 diabetes: a cross-sectional study. Issue 1 (December 2016) - Bernelot Moens, Sophie; Stoekenbroek, Robert; van der Valk, Fleur; Verweij, Simone; Koelemay, Mark; Verberne, Hein; Nieuwdorp, Max; Stroes, Erik
Abstract Background Patients with peripheral artery disease (PAD) are at increased risk of secondary events, which is exaggerated in the presence of type 2 diabetes mellitus. Diabetes is associated with a systemic pro-inflammatory state. We therefore investigated the cumulative impact of PAD and type 2 diabetes on carotid arterial wall inflammation. As recent data suggest a detrimental role of exogenous insulin on cardiovascular disease, we also included a group of insulin users. Results 18 F-fluorodeoxyglucose positron emission tomography with computed tomography (18 F-FDG PET/CT) imaging showed increased carotid arterial wall inflammation, assessed as target-to-background ratio (TBR), in PAD patients without diabetes (PAD-only:n  = 11, 1.97 ± 0.57) compared with matched controls (n  = 12, 1.49 ± 0.57;p  = 0.009), with a significant further TBR increase in PAD patients with type 2 diabetes (PAD-DM, n  = 23, 2.90 ± 1, p  = 0.033 vs PAD-only). TBR of insulin users (n  = 12, 3.31 ± 1.14) was higher compared with patients on oral medication only (n  = 11, 2.44 ± 0.76, p  = 0.035), despite comparable PAD severity (Fontaine stages), BMI and CRP. Multivariate regression analysis showed that Hba1c and plasma insulin levels, but not dose of exogenous insulin, correlated with TBR. Conclusions Concurrent diabetes significantly augments carotid arterial wall inflammation in PAD patients. A further increase in those requiring insulin was observed, which was associated with diabetes severity, rather than with the use of exogenous insulin itself.